(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article describes simultaneous interpretation, using synchronous translation stages with conventional hardware, provision of a sound-proof cabin for the work of a simultaneous interpreter and simultaneous perception in simultaneous interpretation.